Bonding and bridging social capital in the recovery of severe mental illness: a synthesis of qualitative research. (4th May 2019) - Salehi, Asiyeh; Ehrlich, Carolyn; Kendall, Elizabeth; Sav, Adem
Abstract: Background: Social networks are known to have a major influence on the recovery journey of people with severe mental illness (SMI). Aims: To understand the role of bonding and bridging social capital in the recovery process following SMI and to identify the barriers that prevent social networks from being mobilized. Method: A review of major electronic databases for qualitative studies from 2006 to 2015 (41 papers) was undertaken for thematic synthesis. Result: The main themes for bonding social capital included: a buffer for isolation and loneliness, variations depending on illness stages, balance in relationships and connections as a source of self-management. Main themes for bridging social capital comprised: feeling powerless and excluded from community/health care, social care beyond the illness, social care barriers and social inclusion through community groups. Conclusion: All those involved in the management of SMI must be aware of how social support networks hinder or contribute to recovery. People with SMI need opportunities to form reciprocal relationships and sustain supportive networks that can assist them to endure the challenges presented by SMI.